Comment on: "Peatland carbon stocks and burn history: Blanket bog peat core evidence highlights charcoal impacts on peat physical properties and long‐term carbon storage, " by A. Heinemeyer, Q. Asena, W. L. Burn and A. L. Jones (Geo: Geography and Environment 2018; e00063). Issue 1 (19th June 2019) - Evans, Chris D.; Baird, Andy J.; Green, Sophie M.; Page, Susan E.; Peacock, Michael; Reed, Mark S.; Rose, Neil L.; Stoneman, Rob; Thom, Tim J.; Young, Dylan M.; Garnett, Mark H.
Abstract : A recent paper by Heinemeyer et al. (2018) in this journal has suggested that the use of prescribed fire may enhance carbon accumulation in UK upland blanket bogs. We challenge this finding based on a number of concerns with the original manuscript including the lack of an unburned control, insufficient replication, unrecognised potential confounding factors, and potentially large inaccuracies in the core dating approach used to calculate carbon accumulation rates. We argue that burn‐management of peatlands is more likely to lead to carbon loss than carbon gain. e00075